(untitled) (Research, Society and Development, 2025)
The aim of this study was to analyzed the correlation between academic training (PhD, master’s degree, specialty) and the scientific production of Ecuadorian university professors in public universities between 2015 and 2019. A bibliometric research was carried out, in a study of the quantitative and statistical analysis of scientific production using the support of the PRISMA systematic review methodology. The number of professors fluctuated between 18 811 and 20 491 during the period analyzed. Results indicated a generally positive, though not uniform, relationship between academic qualifications and research output. The strongest and most significant correlation was found between the number of scientific articles and book chapters (r = 0.983). While professors with PhDs tend to have higher publication rates, the relationship is not always consistent. The study concludes that, although advanced degrees are typically associated with increased scientific production, factors such as the quality of training, institutional support, and available resources are crucial in maximizing high-quality research outcomes in Ecuador.